Reconstruction of the Biography of G. K. Ozhigov in the Context of the Revolutionary Events of 1905–1917 in Russia - Bekhterev, Sergei L.; Bekhtereva, Lyudmila N. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2024)
Referring to regional material, this article actualizes the tradition of studying the biographies of historical figures in the context of an institutional concept, which makes it possible to describe and explain the controversial facts of political history of the new time in the era of mass social movements. The authors aim to reconstruct the later imperial period (until October 1917) of the life of Grigorii Kondratyevich Ozhigov, a representative of the national revolutionary cohort, who took an active part in the events that occurred in the Urals, Ukraine, the Baltics, Finland, and other areas of the former Russian Empire in the late twentieth century. Methodologically, the work relies on the modernization paradigm, the “new social history”, and related everyday discourse, including the anthropological approach, historical, and biographical methods. Since G. K. Ozhigov’s biography studied by a few Ural historians is replete with inaccuracies, the study is based on sources which have never been referred to previously, including official documents, periodicals, sources of personal origin, autobiographies, and memoirs by Ozhigov himself. The documents kept in the fund of the Ozhigov family of the Central State Archive of the Udmurt Republic are characterized by a complex nature. The study demonstrates that Ozhigov, who came from a peasant family, a worker of Izhevsk factories, managed to rise first to the interregional, and in 1917, to the all-Russian level, reaching the status of a member of the All-Russian Central Executive Committee of the first convocation. In the political sphere, he passed a difficult path of evolution from a militant of the Ural Lbovtsy partisans during the First Russian Revolution of 1905–1907, to a member of the RCP(b) and an active participant in the implementation of the project of the proletarian state.